The secondary metabolite hydrogen cyanide protects Pseudomonas aeruginosa against sodium hypochlorite-induced oxidative stress - da Cruz Nizer, Waleska Stephanie; Adams, Madison Elisabeth; Inkovskiy, Vasily; Beaulieu, Carole; Overhage, Joerg (Frontiers in Microbiology, 2023)
The high pathogenicity of Pseudomonas aeruginosa is attributed to the production of many virulence factors and its resistance to several antimicrobials. Among them, sodium hypochlorite (NaOCl) is a widely used disinfectant due to its strong antimicrobial effect. However, bacteria develop many mechanisms to survive the damage caused by this agent. Therefore, this study aimed to identify novel mechanisms employed by P. aeruginosa to resist oxidative stress induced by the strong oxidizing agent NaOCl. We analyzed the growth of the P. aeruginosa mutants katA, katE, ahpC, ahpF, msrA at 1 g/mL NaOCl, and showed that these known H2O2 resistance mechanisms are also important for the survival of P. aeruginosa under NaOCl stress. We then conducted a screening of the P. aeruginosa PA14 transposon insertion mutant library and identified 48 mutants with increased susceptibility towards NaOCl. Among them were 10 mutants with a disrupted nrdJa, bvlR, hcnA, orn, sucC, cysZ, nuoJ, PA4166, opmQ, or thiC gene, which also exhibited a significant growth defect in the presence of NaOCl. We focussed our follow-up experiments (i.e., growth analyses and kill-kinetics) on mutants with defect in the synthesis of the secondary metabolite hydrogen cyanide (HCN). We showed that HCN produced by P. aeruginosa contributes to its resistance towards NaOCl as it acts as a scavenger molecule, quenching the toxic effects of NaOCl.